GROUP GUIDANCE PLUS ASSERTIVENESS TRAINING TO IMPROVE STUDENTS’ INTERPERSONAL COMMUNICATION: ONE-GROUP PRETEST–POSTTEST STUDY - Lailatul Karimah; Nasruliyah Hikmatul Maghfiroh; Bhennita Sukmawati (EDUCATIONE, 2026)
Many vocational high school students experience barriers to interpersonal communication, such as low self-confidence and reluctance to express their opinions, while group guidance using assertiveness training has been recognized as an effective approach to address these challenges. This study aimed to examine the effectiveness of group guidance with assertiveness training in improving students’ interpersonal communication skills. The research employed a pre-experimental one-group pretest–posttest design involving eight purposively selected 11th-grade students from a total of 32 at SMK Abdul Aziz. A validated interpersonal communication questionnaire was used to collect data, which were analyzed using the Wilcoxon Signed Rank Test. The findings revealed that all participants showed improvement (positive ranks = 8; negative = 0; ties = 0); the mean score increased from M = 97.6 (SD = 7.5) to M = 136.0 (SD = 7.2), indicating a gain of 38.4 points. The Wilcoxon test produced Z = −2.527, p = .012 (< .05), confirming a statistically significant difference between pretest and posttest results. These outcomes demonstrate that group guidance incorporating assertiveness training effectively enhances vocational students’ interpersonal communication. The study provides empirical support for counselors and educators to integrate assertiveness training into preventive and developmental counseling services, contributing to a more positive communication climate in schools. Future research should involve larger samples and control groups, extend intervention periods to assess long-term effects, and explore related psychosocial variables such as self-confidence, social anxiety, and problem-solving skills.